Root Architecture, Propagation Method and Citrus Tree Growth - Ute Albrecht; Sameer Pokhrel; Kim Bowman (EDIS, 2020)
This article presents results from nursery and field studies conducted to determine whether cuttings and tissue culture propagation of rootstocks are suitable alternatives to seed propagation in commercial citrus production. Information on root architectures and aboveground traits of excavated trees is provided and the impacts of propagation method and rootstock cultivar are discussed.